2018
DOI: 10.3389/fphys.2018.01310
|View full text |Cite
|
Sign up to set email alerts
|

RBPs Play Important Roles in Vascular Endothelial Dysfunction Under Diabetic Conditions

Abstract: Diabetes is one of the major health care problems worldwide leading to huge suffering and burden to patients and society. Diabetes is also considered as a cardiovascular disorder because of the correlation between diabetes and an increased incidence of cardiovascular disease. Vascular endothelial cell dysfunction is a major mediator of diabetic vascular complications. It has been established that diabetes contributes to significant alteration of the gene expression profile of vascular endothelial cells. Post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 116 publications
0
14
0
Order By: Relevance
“…Quaking (QKI) is one of the RBPs related to diabetic cardiomyopathy and atherosclerosis. QKI belongs to the signal transduction and activation of RNA (STAR) family, featuring conserved SH2, SH3, and KH RNA-binding domains and participates in the regulation of pre-mRNA splicing, mRNA nuclear exportation, mRNA stability, protein translation, and signal transduction 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Quaking (QKI) is one of the RBPs related to diabetic cardiomyopathy and atherosclerosis. QKI belongs to the signal transduction and activation of RNA (STAR) family, featuring conserved SH2, SH3, and KH RNA-binding domains and participates in the regulation of pre-mRNA splicing, mRNA nuclear exportation, mRNA stability, protein translation, and signal transduction 19 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, RNA-binding motif protein 3 (RBM3) was found to be vital in osteoblast differentiation (Kim et al, 2018), while heterogeneous nuclear ribonucleoprotein K (HNRNPK) has been found to regulate myoblast proliferation and differentiation (Xu et al, 2018). Concurrently, dysregulation of RBP function is implicated in a number of diseases such as diabetes and vascular dysfunction (Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports suggest that HuR may be directly involved in the intercellular membrane fusion during development and under the pathological conditions: (i) HuR-deficient mice are embryonic-lethal due to defects in placenta development [ 117 ]; (ii) HuR is essential for the skeletal muscle myotube formations during embryogenesis [ 118 , 119 ]; (iii) HuR contributes to the post-natal pathological angiogenesis via the regulation of pruning of the vascular branches and the endothelial cell self-fusion during this process [ 88 , 120 , 121 , 122 ]; on the other hand, HuR dimerization may promote atherosclerosis and may enhance the permeability of the vascular endothelial layer [ 123 ]; (iv) HuR is essential for the formation of germ cell syncytium where cells stay connected to one another by intercellular bridges [ 124 ]; (v) under the hypoxic condition, HuR enhances epithelial-to-mesenchymal transition, which is associated with intra- and intercellular microtubule formations and could be suppressed by inhibitors of HuR nuclear/cytoplasmic shuttling [ 125 , 126 ]; (vi) HuR promotes integrity of the gap-junction and the stability of Cx43 transcripts, which are involved in the type ii intercellular tunneling nanotube and microtube formations [ 127 , 128 , 129 ]. Collectively, HuR protein dimerization and translocation from the nucleus to the cytoplasm is associated with cell reprogramming toward cell differentiation and intercellular membrane fusion on several occasions during normal development.…”
Section: Potential Pharmacological Modulators Of Cell Fusionmentioning
confidence: 99%